2007
DOI: 10.1038/sj.ejcn.1602792
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lactobacillus plantarum enteral feeding on the gut permeability and septic complications in the patients with acute pancreatitis

Abstract: Objective: To study the effect of the Lactobacillus plantarum (LP) enteral feeding on the gut permeability and sepsis in the patients with acute pancreatitis. Subjects: Seventy-six subjects who stayed over 1 week in the hospital completed the study. Subjects were not treated with any lactobacillus supplement before the intervention. Methods: Seventy-six patients with acute pancreatitis were randomly divided into two groups, parenteral nutrition (PN) group (n ¼ 38) and ecoimmunonutrition (EIN) group supplied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(91 citation statements)
references
References 31 publications
2
82
0
3
Order By: Relevance
“…Four RCTs were not included in the above meta-analyses as they were not able to be statistically aggregated, directly or indirectly, with any other RCTs 36,43,49,50 . One RCT 49 .…”
Section: Studies Not Included In the Meta-analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…Four RCTs were not included in the above meta-analyses as they were not able to be statistically aggregated, directly or indirectly, with any other RCTs 36,43,49,50 . One RCT 49 .…”
Section: Studies Not Included In the Meta-analysesmentioning
confidence: 97%
“…Patients received (semi)elemental formulation in nine arms of the included trials 7,33,34,38,39,42,46,47,50 , polymeric formulation in seven arms 7,35,36,41,43,45,49 , fibre-enriched enteral formulation in six arms 10,37,40,44,48,49 , enteral nutrition supplemented with probiotics in four arms 10,40,48,50 , and immunonutrition (glutamine, arginine and omega-3 fatty acids) in three arms 37,43,44 . The 20 RCTs comprised a total of 1070 patients with acute pancreatitis (825 with severe and 245 with mild course of acute pancreatitis).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Finally, studies were also checked for a follow-up period, to speculate on the persistence of a beneficial effect of probiotics. Only two studies specifically defined a follow-up test but neither of both tested the intestinal permeability at that time [45,46]. Although the clinical symptoms remained lower in the probiotics group, nothing can be said about the persistent effects on intestinal permeability.…”
Section: Probiotic Regimementioning
confidence: 99%
“…For example, in experimental models of colitis, several species of probiotics including Lactobacillus, Escherichia coli, and Bifidobacterium can reduce gut permeability by upregulating trans-membrane proteins that are important in preserving tight junctions between epithelial cells. [30][31][32][33] It has also been shown that treatment with these probiotics can enhance mucus production and consequently improve the physical barrier protecting the epithelial layer. 34,35 Products of bacterial fermentation can also play an important role in maintaining the intestinal barrier.…”
Section: Effect Of Gut Microbiota On Intestinal Permeabilitymentioning
confidence: 99%